A native chromatin extraction method based on salicylic acid coated magnetic nanoparticles and characterization of chromatin. Issue 3 (5th December 2014) - Zhou, Zhongwu; Irudayaraj, Joseph
Abstract : Native chromatin extraction with salicylic acid coated magnetic particles was achieved. Abstract : Native chromatin contains valuable genetic, epigenetic and structural information. Though DNA and nucleosome structures are well defined, less is known about the higher-order chromatin structure. Traditional chromatin extraction methods involve fixation, fragmentation and centrifugation, which might distort the higher-order structural information of native chromatin. We present a simple approach to isolate native chromatin from cultured mammalian cells using salicylic acid coated magnetic nanoparticles (SAMNPs). Chromatin is magnetically separated from cell lysates without any filtration or high-speed centrifugation. The purified chromatin is suitable for the examination of histone modifications and other chromatin associated proteins as confirmed by western blotting analysis. The structure of chromatin was determined by confocal fluorescence microscopy, transmission electron microscopy (TEM) and atomic force microscopy (AFM). High-resolution AFM and TEM images clearly show a classical bead-on-a-string structure. The higher-order chromatin structure is also determined via electron microscopy. Our method provides a simple, inexpensive and an environmentally friendly means to extract native chromatin not possible before, suitable for both biochemical and structural analysis.